Effect of dexamethasone as an analgesic adjuvant to multimodal pain treatment after total knee arthroplasty: randomised clinical trial. (4th January 2022) - Gasbjerg, Kasper Smidt; Hägi-Pedersen, Daniel; Lunn, Troels Haxholdt; Laursen, Christina Cleveland; Holmqvist, Majken; Vinstrup, Louise Ørts; Ammitzboell, Mette; Jakobsen, Karina; Jensen, Mette Skov; Pallesen, Marie Jøhnk; Bagger, Jens; Lindholm, Peter; et al.
Abstract: Objective: To investigate the effects of one and two doses of intravenous dexamethasone in patients after total knee arthroplasty. Design: Randomised, blinded, placebo controlled trial with follow-up at 90 days. Setting: Five Danish hospitals, September 2018 to March 2020. Participants: 485 adult participants undergoing total knee arthroplasty. Intervention: A computer generated randomised sequence stratified for site was used to allocate participants to one of three groups: DX1 (dexamethasone (24 mg)+placebo); DX2 (dexamethasone (24 mg)+dexamethasone (24 mg)); or placebo (placebo+placebo). The intervention was given preoperatively and after 24 hours. Participants, investigators, and outcome assessors were blinded. All participants received paracetamol, ibuprofen, and local infiltration analgesia. Main outcome measures: The primary outcome was total intravenous morphine consumption 0 to 48 hours postoperatively. Multiplicity adjusted threshold for statistical significance was P<0.017 and minimal important difference was 10 mg morphine. Secondary outcomes included postoperative pain. Results: 485 participants were randomised: 161 to DX1, 162 to DX2, and 162 to placebo. Data from 472 participants (97.3%) were included in the primary outcome analysis. The median (interquartile range) morphine consumptions at 0-48 hours were: DX1 37.9 mg (20.7 to 56.7); DX2 35.0 mg (20.6 to 52.0); and placebo 43.0 mg (28.7 to 64.0). Hodges-Lehmann median differences between groups were: −2.7 mg (98.3% confidence interval −9.3 to 3.7), P=0.30 between DX1 and DX2; 7.8 mg (0.7 to 14.7), P=0.008 between DX1 and placebo; and 10.7 mg (4.0 to 17.3), P<0.001 between DX2 and placebo. Postoperative pain was reduced at 24 hours with one dose, and at 48 hours with two doses, of dexamethasone. Conclusion: Two doses of dexamethasone reduced morphine consumption during 48 hours after total knee arthroplasty and reduced postoperative pain. Trial registration: Clinicaltrials.gov NCT03506789 .